E-Commerce As Marketing Media for Home Industry Products: E-Commerce Sebagai Media Pemasaran Produk Industri Rumah Tangga - Andrianof, Harkamsyah (KPN Kopertis X, 2024)
This community service aims to help groups of housewives who experience difficulties in marketing their products. So far, housewife groups only market it to stalls around the village or traditional markets. Sometimes waiting for special orders for certain events, and this is not fixed. As a result of limited product marketing, the economic output generated by the housewife group is not optimal. The Community Service Team has prepared activities to overcome problems that arise for groups of housewives by providing training on application use mobile ecommerce in marketing products. Product marketing with mobile e-commerce because this application can be used on smartphone / Smartphones are available to almost everyone, including housewives, who on average also have smartphones. With training given to groups of housewives in terms of use mobile with the application e-commerce then this group of housewives are already using it e-commerce which makes it easier and faster to sell the products they have produced. So that the results obtained from this training were an increase in product sales and from previous sales and the economy of the housewife group increased. Apart from that, it is also easier for housewives to market their products with applications mobile ecommerce.